2022
DOI: 10.1002/adbi.202101301
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Discovery of Therapeutics to Curtail Islet Amyloid Polypeptide Aggregation for Type 2 Diabetes Treatment

Abstract: Table 2. Continued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 150 publications
0
6
0
Order By: Relevance
“…Also, cell viability assays proved that the protection effect on pancreatic INS-1 cells imposed by these compounds in T2D patients follows the order caffeic acid > chlorogenic acid > caffeine . Cichoric acid, a derivative of caffeic acid, also targets the residues of hIAPP via electrostatic and π–π stacking . Brazilin has also displayed amyloid inhibition, delay of conformational transition, and fibril disruption of hIAPP and Aβ .…”
Section: Anti-amyloid Activity Of Natural Polyphenolsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, cell viability assays proved that the protection effect on pancreatic INS-1 cells imposed by these compounds in T2D patients follows the order caffeic acid > chlorogenic acid > caffeine . Cichoric acid, a derivative of caffeic acid, also targets the residues of hIAPP via electrostatic and π–π stacking . Brazilin has also displayed amyloid inhibition, delay of conformational transition, and fibril disruption of hIAPP and Aβ .…”
Section: Anti-amyloid Activity Of Natural Polyphenolsmentioning
confidence: 99%
“…Other green tea extracts, such as catechin, epicatechin, gallocatechin gallate (GCG), epicatechin gallate (ECG), and epigallocatechin (EGC) (Figure ), also display anti-amyloidogenic properties by directly binding with the steric zipper of the fibrillar segments to freeze fibrillation . A molecular dynamics (MD) study showed that the ability of three stereoisomeric catechins to disrupt and bind with Aβ 42 protofibrils follows the order (−)-catechin > (+)-catechin > epicatechin (Figure ).…”
Section: Anti-amyloid Activity Of Natural Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary sequence of the peptide is extremely conserved in organisms, for example, human and mouse IAPPs differ by only six amino acids. The formation of IAPP deposits is intrinsically associated with type 2 diabetes (T2D) because more than 70% diabetic patients present this type of amyloid formation [ 32 ]. The number of aggregates appears to be correlated with the pathology severity, as evidenced by autopsies.…”
Section: The Hallmark Lesions Of Ad: β-Amyloid and Tau Proteinsmentioning
confidence: 99%